The Overserving Parenting Patterns and Their Impact on Early Childhood Development: Pola Pengasuhan yang Terlalu Melayani (Overservice) dan Dampaknya Terhadap Perkembangan Anak Usia Dini - Sundari, Sri; Febrilyan, Ryan; Grahani, Puri (Edusiana: Jurnal Ilmu Pendidikan, 2025)
This study examines the parental caregiving pattern of overservice and its impact on early childhood development. Overservice, often characterized by parents excessively fulfilling all of their child’s needs, can influence the emotional, social, and cognitive development of the child. The research methodology used is a literature review, aiming to identify and analyze existing studies on this caregiving pattern and its effects on child development. This study also reviews developmental psychology theories, including Erikson's and Vygotsky's theories, and Baumrind’s typology of parenting styles (authoritarian, permissive, and authoritative) to explore how an overindulgent caregiving approach can affect a child's ability to develop independence, self-regulation, and social skills. Factors analyzed include parental personality, involvement in caregiving, and family dynamics. The findings suggest that an overservice caregiving style may lead to difficulties in a child’s ability to handle challenges, develop a sense of responsibility, and increase the likelihood of dependency and social skill deficits. The study concludes that a balanced approach to parenting, which allows space for children to learn independence and face challenges, better supports healthy emotional and social development in early childhood.